CADEXOMER VERSUS POVIDONE IODINE DRESSING IN CHRONIC LEG ULCERS- A PROSPECTIVE STUDY. - Raj, Ayush; Raj, Ankit; Singh, Sakshi; Tajdar, Yasir; Bhushan, Vibhuti; Jha, Pawan Kumar; Abhishek, K (Student’s Journal of Health Research Africa, 2023)
Background: In the present scenario the entire healthcare system has been overburdened with chronic wounds be it monetary wise or manpower requirements like nurses, doctors, etc. A chronic wound is being treated by many topical drugs which are prevailing in the market. So we considered this study i.e. “the effect of cadexomer and providone iodine on chronic leg ulcers”. Objective: The main and primary objective of this study was to compare the outcome of both, Cadexomer and povidone-iodine, about their effect on the treatment of leg ulcers. Methods: With 30 patients in each group, 30 patients with chronic wounds participated in this prospective study. As part of the statistical analysis, Pearson’s Correlation Coefficient and the Student’s Paired T-Test are used. Results: Patients who received cadexomer iodine ointment had a significantly (p<0.05) greater rate of wound healing, as well as a significantly lower level of bacterial overload and promotion of the creation of granulation tissue. Conclusion: The effect of cadexomer as a vector in combination with providone iodine ointment resulted in a higher rate of biofilm, slough, and debris reduction and a better rate of granulation tissue formation promotion, both of which increased the rate at which a wound heals and lowered the cost of managing chronic wounds. Recommendation: It is recommended that the efficacy of the ointments (cadexomer and providone iodine) be researched for proper healing of ulcers and wounds in diabetic leg ulcers because a significant number of diabetic patients experience leg ulcers because, in this study, it was discovered that over 60 people suffered with the risk of leg ulcers.